Effectiveness of Mind–Body–Based Psychoeducation in Strengthening Midwives’ Role and Enhancing Breastfeeding Self-Efficacy Among Postpartum Mothers: A Quasi-Experimental Study - Manullang, Rasmi; Tarigan, Imarina; Nainggolan, Anna Waris; Aruan, Lasria Yolivia; Sianipar, Yesica Geovany; Damanik, Lira Agnes Monica; Siahaan, Sastra Amelia (Journal of Applied Nursing and Health, 2025)
Background: Breast milk is the best nutrition for babies and has long-term benefits for both mother and child health. A critical factor in successful breastfeeding is breastfeeding self-efficacy (BSE), a mother's confidence in her ability to breastfeed. Methods: This quasi-experimental study employed a pre-test and post-test design with a control group and purposive sampling. The sample comprised 60 postpartum mothers: 30 in the intervention group and 30 in the control group. The intervention involved using the PIANA application for four weeks. Statistical tests were performed using SPSS 26 for univariate and bivariate data analysis. Outcomes were measured using the Wilcoxon and Mann-Whitney U tests to assess whether psychoeducation could increase postpartum mothers' confidence in breastfeeding. Results: Bivariate analyses of the variables were conducted using statistical tests after the application, namely the Midwife's Role variable (p = 0.023), the Psychoeducation variable (p = 0.032), and the BSE variable (p = 0.012). The results of the bivariate analysis of the three variables showed that the Midwife's Role with BSE psychoeducation positively affected postpartum mothers' confidence in breastfeeding. Conclusion: Psychoeducational applications using a mind-body approach have been shown to improve breastfeeding self-efficacy in postpartum mothers. Optimizing the role of midwives through this medium can serve as an effective, flexible educational tool to support postpartum mothers in achieving breastfeeding success.